FHIT Doubts are Clear Now. (2010) - Wali, Anjilna
Abstract : The fragile histidine triad ( FHIT ) gene is a bonafide tumor-suppressor gene present on the short arm of chromosome 3 and its loss of function has been evaluated in different types of cancers. Loss of heterozygosity at various sections of the FHIT gene and the methylation analysis of the promoter region showed that it is one of the important and preliminary genetic alterations in the cell, and its restoration in the cell line or nude mice suppresses tumorigenicity. Current research on the FHIT gene has depicted that Fhit interacts with different proteins through different pathways in the nucleus, mitochondria, and cytoplasm, directing the cell to apoptosis.